2022
DOI: 10.3389/fmicb.2022.796758
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Relative Bacterial Richness and Community Composition in Seawater and Marine Sediment Are Robust for Both Operational Taxonomic Units and Amplicon Sequence Variants

Abstract: To understand the relative influences of operational taxonomic units (OTUs) and amplicon sequence variants (ASVs) on patterns of marine microbial diversity and community composition, we examined bacterial diversity and community composition of seawater from 12 sites in the North Atlantic Ocean and Canadian Arctic and sediment from two sites in the North Atlantic. For the seawater analyses, we included samples from three to six zones in the water column of each site. For the sediment analyses, we included over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Microbial communities of the world’s oceans play an important role in the cycles of biogenic elements on the earth and in maintaining biosphere stability. Therefore, due to the development of molecular methods for studying microbial communities, a large number of studies on the diversity of microorganisms in the marine habitats of our planet have appeared, including both 16S rRNA profiling and metagenomic analyses of different marine habitats [ 33 , 34 , 35 , 36 , 37 ]. Among them are many that focus on microbial communities of the Arctic regions and their spatial and seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial communities of the world’s oceans play an important role in the cycles of biogenic elements on the earth and in maintaining biosphere stability. Therefore, due to the development of molecular methods for studying microbial communities, a large number of studies on the diversity of microorganisms in the marine habitats of our planet have appeared, including both 16S rRNA profiling and metagenomic analyses of different marine habitats [ 33 , 34 , 35 , 36 , 37 ]. Among them are many that focus on microbial communities of the Arctic regions and their spatial and seasonal changes.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study revealed a high abundance of bacteria in the phyla Proteobacteria, Bacteroidota, and Cyanobacteria at every sampling site, which corresponded to previous investigations of the microbiome in the seawater of the Gulf of Thailand [ [22] , [23] , [24] ]. These three phyla are also dominant in many other marine environments including the Baltic Sea, Japan Sea, and western North Atlantic [ 21 , 31 ]. However, samples from Prachuap Kiri Khan Province (NHH) showed Thermoplasmatota in high abundance rather than Bacteroidota.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides the first, detailed insight into the composition and the spatial and year-round temporal changes of planktonic and epilithic prokaryotic communities of Danube. High-throughput next generation amplicon sequencing was used with OTU-based calculations applying filters to retain clusters with >0.1% relative abundance, enabling a consistent taxonomy comparison [ 39 42 ].…”
Section: Discussionmentioning
confidence: 99%